Exploring solutions to improve antenatal care in resource-limited settings: an expert consultation - Carlotta Gamberini; Federica Angeli; Elena Ambrosino (BMC, 2022)
Abstract Background Shortage or low-quality antenatal care is a complex and "wicked" problem relying heavily on contextual, socio-cultural, environmental and intersectional aspects. We report the outcome of an expert consultation discussing solutions to improve antenatal care quality, access and delivery in low- and middle-income countries, and providing recommendations for implementation. Methods The social ecological model was used as an analytical lens to map and interpret discussion points and proposed solutions. In addition, a conceptual framework for maternal and neonatal health innovation based on the building blocks of the World Health Organization health system and the Tanahashi Health Systems Performance Model provided a logical overview of discussed solutions. Results Many barriers and norms continue to hinder antenatal care access. From values, beliefs, traditions, customs and norms, to poor resource allocation, there is a need of reshaping health systems in order to provide high quality, respectful maternal and childcare. The burden of poor maternal health, morbidity and mortality is concentrated among populations who are vulnerable due to gender and other types of discrimination, have financial constraints and are affected by humanitarian crises. Conclusions In order to address maternal health issues, good quality and evidence-based services should be guaranteed. Investments in strengthening health systems, including data and surveillance systems and skilled health workforce, should be considered an essential step towards improving maternal health services.